Metall Mining Corporation: A Company In Transition - Klaus M. Zeitler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1990)
INTRODUCTION One cannot discuss the subject of "Raising Capital in the 1990s" without having a crystal ball and a reliable fortune teller. This discusses "Raising Capital for the 1990sW, which is what Metal1 Mining Corporation did in 1987. We raised (3166 million in an IPO (initial public offering) that was originally planned for only some (375 million. Why did we raise this money? How did we do it, and why was this IPO so successful? The answer to the first question requires a description of the promoter and principal shareholder of Metal1 Mining Corporation, Metallgesellschaft AG. This West Germany company was founded over 100 years ago in Frankfurt as a trading house for non-ferrous metals. It has developed into one of the world's leading firms in the non-ferrous metals industry. The company's worldwide activities in all areas of that business include mining, smelting and refining, the trading of ore, base and precious metals, the production of semi-fabricated and finished metal products, and the provision of engineering, construction and transportation services. Metallgesellschaft AG has also diversified into many other areas, the most significant of which are manufacturing, the production of chemicals, the development and application of technical and chemical processes, the planning and construction of industrial plants, and activities associated with finance, insurance, shipping and freight forwarding, and the provision of barter and countertrade services. The company maintains a network of more than 100 offices around the world; it employs some 25,000 people in its worldwide activities. [Selected financial data, as of September 30, 1987: (MetaUgesellschafl AG) Working Capital DM 8%.6 million CDNS 672.8 million Long Term Debt DM 568.0 million CDNS 426.2 million Sales DM 14.9 billion CDNS 11.2 billion Net Income DM 87.7 million CDN$ 65.8 million Market Capitalization at April 27, 1987: (Metallgesellschafi AG) Outstanding Shares ~,6oo,o0o DM 1,875 million CDNS 1,407 million] For the fiscal year ended September 30, 1987, Metallgesellschaft AG had, on a consolidated basis, net sales of DM13.3 billion, net income of DM100 million and total assets of about DM7.0 billion. Metallgesellschaft AG established the American Metal Company, a predecessor of AMAX Inc. one of the largest ventures undertaken by Metallgesellschaft AG then was the acquisition, through the American Metal Company, of a majority share in the Mexican Penoles mine, a large lead and silver deposit. METALLGESELLSCHAFT AG Figure 1 depicts an overview of Metallgesellschaft AG before and at the time the initial public offering of Metall Mining Corporation's shares took place. It shows that mining was far from the centre of Metallgesellschaft's activities. Therefore, it could not expect to receive an extraordinary amount of board attention. Thus, mining investments not only had to compare well with other mining opportunities, but were in fierce competition with projects from other divisions. In addition, mining was sub-divided into two separate departments -- domestic and international. These two departments had different management styles and diverging interests which resulted in a minimum co-operation between them. The domestic mining department was primarily interested in the survival of the local mines. These mines were characterized by rising operating costs and declining ore grades. It took a special commitment and continued ingenuity to develop and adjust to local conditions, and modern mining and processing technology, in order to remain competitive, or at least survive within the international mining industry. Local management